Internet et le Grand Siècle : les recueils collectifs de poésie au regard du Web - Christophe Schuwey (Sillages Critiques)
This article highlights existing but overlooked analogies between digital-age publications – on websites, blogs and social networks – and the multi-authored poetry collections that emerged and thrived in late seventeenth-century France. There are indeed striking similarities between the two formats, in terms both of their composition and their consumption. Much like twenty-first-century blogs, the poetry collections that proliferated in the second half of the seventeenth century resulted in a facilitated access to publication and a transformation of authorship; in both cases, such facilitation also gave rise to violent reactions. While printed books never became quite as adaptable as web pages, still booksellers in the ancien régime saw multi-authored poetry collections as an opportunity to keep with swiftly changing literary trends. Finally, in the same way as digital readers tend to access poems outside their original collections, likewise, readers in the past rarely read a poetry collection from cover to cover, choosing instead this or that poem with a view to sharing it with other readers. These connections between two seemingly opposed periods ultimately highlight the fundamental role of poetry collections as media – a dimension that might indeed become obsolete in the digital age. However, identifying this stratum also reveals what poetry collections possess in their own right, namely an aesthetic dimension that eludes technological change.